Building Information Modeling 2015
DOI: 10.1061/9780784413982.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Augmented Reality into Building Information Modeling for Facility Management Case Studies

Abstract: The management of complex information flow can be a crucial aspect of Facility Management (FM). Because of the increasing complexity of the present-day building projects, FM activities, for example, maintaining a building facility or a system, normally involve enormous human multitasking across different knowledge domains. Lessons learned from the present successful FM instances manifest that the FM teams are increasingly interested in applying more viable technologies to achieve the effective management of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…If the students get information through personal experience and according to Edgar Dale's con of experience, "after two weeks the human brain tends to remember 10% of what is read, 20% of what is heard, 30% of what is seen, and 90% of simulations or personal experience", more research on the actual relation between VR simulation and personal experience could solidify VR as a valid method of teaching. Wang et al showed that using VR for memorization showed an 8.8% improvement overall in recall accuracy using the VR [12]. VR has great potential for the Architecture, Engineering, and Construction industries, as a person can experience realistic firstperson situations without having to care about injuries [13].…”
Section: Discussionmentioning
confidence: 99%
“…If the students get information through personal experience and according to Edgar Dale's con of experience, "after two weeks the human brain tends to remember 10% of what is read, 20% of what is heard, 30% of what is seen, and 90% of simulations or personal experience", more research on the actual relation between VR simulation and personal experience could solidify VR as a valid method of teaching. Wang et al showed that using VR for memorization showed an 8.8% improvement overall in recall accuracy using the VR [12]. VR has great potential for the Architecture, Engineering, and Construction industries, as a person can experience realistic firstperson situations without having to care about injuries [13].…”
Section: Discussionmentioning
confidence: 99%
“…The core of XR implementation is its detailed 3D model, which also requires information on the surrounding environment (Sampaio and Martins 2014). BIM is a multi-dimensional (3D space, 4D time, 5D cost, and ND applications) model information integration technology; therefore, the combination of BIM and XR will be more helpful in promoting the application of XR technology in infrastructurerelative fields (Wang et al 2015). Because of the high-fidelity and implantable characteristics of XR, it is likely to be applied to the planning of infrastructure disaster avoidance systems.…”
Section: Extended Realitymentioning
confidence: 99%
“…When integrating BIM with augmented reality, there are five advantages to FM: intelligent error diagnosis, visual operating instructions, state perception, building performance monitoring, and portable path instructions. Figure 14 illustrates the application areas and benefits of BIM + AR in FM [38].…”
Section: E the Augmented Reality (Ar) In Fmmentioning
confidence: 99%
“…In this case study [38], the application of AR in facility management was studied to the MRI room in the health care project located in Perth. The model of the room was prepared using BIM Application, then they set the locations of virtual reality visualization equipment on different patches of the room, the hidden tubes model was installed in the shape, the air conditioning units were represented, and the MRI equipment was located in the model, as shown in Figure 15.…”
Section: A Case Study: Integration Of Ar In Health Fmmentioning
confidence: 99%